Barriers in Implementing Zero Energy Building Policies in the United Arab Emirates - Ather, Syed Waqas (2019)
It is a well-known fact that human activities over the past few decades have led to the cause of climate change. Building sector is responsible for approximately 28% of the overall carbon emissions. To tackle this, several initiatives such as the Sustainable Development Goals are in place to make cities and human settlement inclusive, safe, resilient, and sustainable. In the building sector, Zero Energy Buildings (ZEB) can have a huge impact by demanding a combination of both energy efficiency measures, and reliance on renewable energy generation. Even though, there are examples of ZEB in the European Union, and the United States of America (USA). United Arab Emirates (UAE) is yet to explore the concept of ZEB in entirety. The aim of this paper is to identify the barriers, and challenges in implementing ZEB policies in the UAE. Economic barriers such as the high upfront construction costs, longer payback periods, and need of sustainable model that consider short-term and long-term goals of ZEB were the main barriers identified through a survey. Also, lack of ZEB codes and standards are also seen as a barrier to implement ZEB policies. Reliance on on-site renewable energy for high-rise residential buildings is seen as a challenge to ZEB. For future legislations pertaining to ZEB in the UAE, the existing codes and standards must coexist with the ZEB codes and standards. Also, the targets set for the ZEB must be coherent with the existing strategies such as the UAE Clean Energy Strategy 2050.